(untitled) (Journal of Information Technologies in Education (ITE), 2015)
The article devoted to a research of influence of progress in Informatics and relative to it disciplines to the showings of educational progress. It has been analyzed the scientific attitude to the definition of term «educational progress». It has been substantiated that computer and information competency of future lawyers is not only a partial of professional activities but also a powerful tool of information tasks with educational character solving by a student in the process of his professional training in the university, that is displayed by the readings of educational progress.During the research we have received the value of coefficient of correlation between the values of final marks in the disciplines Informatics, Legal information retrieval systems, Legal statistics and the results of end-of-semester exams from the first to the forth course, the average score and quality coefficient of students’ education progress in the control and experimental groups. During the research of influence of level of formedness of computer and information competency of future lawyers on the readings of the final progress in the educational subjects it has been established that: the level of formedness of base component of computer and information competence, that is provided by the learning of Informatics discipline on the information stage of working of system of professional computer and information training have positive influence on the showings of students’ final progress in education subjects. This process is more effective in the experimental groups and to a greater extent it influences the coefficient of final progress quality than its average score; this influence especially visible is on the social and economic and humanitarian disciplines, it is confirmed by value of calculated coefficients of correlation; at the axiological stage of system function of professional computer and informational training the maximum values of the coefficients of correlation (0.84-0.88) are typical for special and legal disciplines that have a key role for the formation of professional competence of a future lawyer; freedom from negative coefficients in the regression equations for the average score and quality coefficient of the final progress at the converting stage of working of system of computer and information training shows that there is an influence of the level of formedness of computer and information competency of future lawyers on the readings of the final progress of all without distinction disciplines, the learning of which falls in the same time interval with the converting stage of system function of computer and informational training of future lawyers; the average score and quality coefficient of the final progress with education disciplines in the experiment group is higher than in the control group, besides it is seen higher dynamics of average score growth, especially of the quality coefficient in the experiment group, which can be explained by the effect of working of system of computer and information training of future lawyers.